Applications of Remote Sensing and Sensor Technology for Unmanned Aerial Vehicle - Liu, Zheyu (Transactions on Environment, Energy and Earth Sciences, 2024)
As a relatively new remote sensing means, unmanned aerial vehicle (UAV) remote sensing has been widely used in the fields of agriculture, forestry, and urban construction surveying and mapping because of its low cost, high efficiency, and flexibility. This paper introduces UAV remote sensing sensor technology and its applications in different fields. First, the core role of sensors in UAV remote sensing systems is introduced, including the development of multispectral, hyperspectral, and LiDAR sensor technologies and their applications in UAV remote sensing. Then, the working principles, technical characteristics, and application scenarios of multispectral, hyperspectral, and LiDAR sensors are discussed. Then, multi-sensor integration techniques in UAV remote sensing are discussed in terms of their importance and challenges. Finally, through the application cases of agricultural monitoring, forestry resource management, and urban construction mapping, the practicality and potential of UAV remote sensing technology are shown. This paper provides a reference for the research and application of UAV remote sensing and its sensor technology in several fields. With the continuous progress and innovation of technology, UAV remote sensing technology is expected to play a key role in more fields and promote the sustainable development of related industries.